Effects of Tongue Plate on the Nasomaxillary Complex of Patients with Unilateral Cleft Lip and Cleft Palate - S Eslami; R Showkatbakhsh; M Narimani; Z Kamalee; A Jamilian (Islamic Azad University, 2017)
Background and aim: Cleft lip and cleft palate are among the most common orofacial abnormalities. Patients with these deformities commonly present with midface deficiency and need challenging treatment modalities that focus on improving the position of the maxilla. Tongue plate appliance is an intraoral device that has shown promising results in the treatment of growing patients with maxillary deficiency. Nonetheless, the effects of tongue plate on patients with cleft lip and cleft palate have not been evaluated yet. This study aimed to assess the effects of tongue plate on growing patients with cleft lip and palate. Materials and methods: Twenty-four growing patients (12 girls and 12 boys) with non-syndromic unilateral cleft lip and cleft palate between the ages of 6-12 years volunteered to participate in this quasi-experiment. All the patients had undergone the preliminary stages of lip and palate closure during infancy, but none of them had received bone grafts. They were treated with tongue plate appliance for 18±3 months. Lateral cephalograms were obtained and were analyzed at the beginning and at the end of the treatment. Paired t-test was used for statistical analysis of normally-distributed data; otherwise, Wilcoxon test was used. Results: Paired t-test showed that the Sella-Nasion-Point A (SNA) angle was increased from 76.3±0.2 to 77.3±0.14 degrees, and the Point A-Nasion-Point B (ANB) angle was enhanced from -2.26±0.17 to 0.93±0.82 degrees (P<0.001). Conclusion: Tongue plate appliance has shown favorable results in the treatment of class 3 malocclusion and maxillary deficiency in growing patients with cleft lip and cleft palate.